Effect of Addition of Rare Earth Element Cerium on the Microstructure and Mechanical Properties of Microalloyed Peritectic Grade Steel - Kumar V.; Deva A.; Chattopadhyay K. (My University, 2025)
Non-metallic inclusions in steel negatively affect operational processes and mechanical properties based on their morphology, size, physical state and distribution. Inclusion modification is especially important when sulphur levels are high because the sulphides that form can affect the operational process more significantly than the unmodified inclusions themselves. This research is an attempt to examine the impact of cerium addition on tensile and impact toughness properties, grain size, inclusion composition, morphology and fracture surface of microalloyed peritectic grade steel. The impact toughness at − 40 °C significantly increased by 139 and 164% and yield strength improved from 431 to 495 and 483 MPa with the addition of 0.015 and 0.045 wt% cerium, respectively. The improvement in mechanical properties has been attributed to the combined effect of altering the shape and composition of inclusions, refinement in grain size and uniform dispersion of inclusion in matrix. © The Indian Institute of Metals - IIM 2024.